EVALUATION OF THE EFFECTIVENESS OF ALTERNATIVE TREATMENTS FOR MENOPAUSAL SYMPTOMS IN POSTMENOPAUSAL WOMEN - S. V. Yureneva; E. I. Ermakova (Медицинский совет, 2017)
Menopause is the final cessation of menstrual cycles due to loss of follicular activity of the ovaries. According to the results of a meta-analysis of 36 studies performed in 35 countries, the average age of menopause onset is 48.8 years (95% CI 48,3 – 49,2) with significant fluctuations of this indicator depending on the geographical region of residence of women: lower in Africa, Latin America and middle East countries (47,2–48.4 years) and later in Europe and Australia (50,5–51,2 year) [1]. The number of women in peri- and postmenopausal phase in connection with the increase in life expectancy is increasing. In Russia it is currently more than 21 million. The average age of the menopause onset in Russia ranges from 49 to 51 years, at the same time women live in conditions of estrogen deficit for 1/3 of their life [2, 3].